Impact of satellite clinics on geographic access to assisted reproductive technology services in the United States - Micajah Z. McGarity; Christopher N. Herndon; John A. Harris; Benjamin F. Hobbs (BMC, 2022)
Abstract Background Many assisted reproductive technology (ART) centers utilize satellite clinics to expand reach and access to clinical services, but their contribution to lowering geographic barriers in access to care has not been examined. This study's purpose is to determine the extent to which satellite clinics impact geographic access to ART and estimate the percentage of reproductive-age women who have geographic access to ART services. Methods A systematic web-search collected the locations of all main and satellite ART clinics in the United States (US). Driving times were calculated between satellite clinics and main clinics. The percentage of women with geographic access to care was characterized by clinic type using US Census Core Based Statistical Areas (CBSAs). Logistic regression was used to statistically model the presence of main and satellite clinics as a function of CBSA median income and female reproductive-age population. Results Four hundred sixty-nine main clinics with embryology labs and 583 satellite clinics were found in the US. Practices with satellite clinics tend to perform more ART cycles. Satellite clinics are located on average 66 minutes from their practice's main clinic and 31 minutes from any main clinic. 22% of satellite clinics were in CBSAs without a main clinic. 46 M (72%) US reproductive-age women live in a CBSA with a main clinic, 5.1 M (8%) women live in a CBSA without a main clinic but at least one satellite clinic, and 13 M (20%) women live in an area with no ART clinic of either type. Female reproductive-age population was found to be a more important predictor of clinic presence than median income. Conclusions The majority of satellite clinics in the US are positioned in relative proximity to a main clinic. 85% of satellite clinics are located closer to the main clinic of other practices than to their own main clinic. Less than a quarter of ART satellite clinics expand geographic access to ART services by being located in areas without a main clinic, and the vast majority of practices with satellite clinics position their satellite clinics close to another practice's main clinic. Trial registration Not applicable.